Relationship between irregular diet and risk of esophageal cancer: A meta-analysis - Guan, Jiayun; Pan, Xixin; Ruan, Shenghang; He, Xiaopeng; Xu, Yuhao; Rong, Xiaoxiang; Ou, Yanhua (Frontiers in Genetics, 2022)
Background: Associations between irregular diet and the risk of esophageal cancer remain unclear. The current meta-analysis was performed to determine whether the presence of irregular diet increases the risk of esophageal cancer. Methods: The data from PubMed, Cochrane Libraries, and Embase up to 23 January 2022 were included in our analysis to identify studies that investigated associations between irregular diet and the risk of esophageal cancer. Summary relative risk (RR) and 95% confidence intervals (CIs) were calculated using a random-effects model. Results: Five cohort studies and one case-control study investigating associations between irregular diet and the risk of esophageal cancer were included. None of the articles demonstrated publication bias. The summary RR was 4.181 (95% CI 2.196–7.960, I2 = 66.1%, p = 0.011). In the subgroup analysis, we found significant heterogeneity in the Non-disease-causing group, nurse group and Asian group. The above three that produce heterogeneity may be the source of heterogeneity in the results of this study. Conclusion: The current meta-analysis indicates that irregular diet increase the risk of esophageal cancer. Trial registration: (https://www.crd.york.ac.uk/prospero/), (PROSPERO, CRD42022306407)